Thrombopoietin concentrations are low in patients with cirrhosis and thrombocytopenia and are restored after orthotopic liver transplantation. Issue 5 (1st May 1999) - Goulis, J; Chau, T N; Jordan, S; Mehta, A B; Watkinson, A; Rolles, K; Burroughs, A K
Abstract : BACKGROUND: Thrombocytopenia in cirrhotic patients may be due to deficient production of thrombopoietin. AIMS: To determine the relation between thrombopoietin and thrombocytopenia in cirrhotic patients before and after orthotopic liver transplantation. METHODS: Thrombopoietin concentrations and platelet counts were measured in 43 cirrhotic patients and 21 normal controls and serially for 14 days after transplantation in 23/43 patients. RESULTS: 27 of the 43 patients had thrombocytopenia (platelet count less than 120 × 10 9 /l; group 1) whereas 16 patients had normal platelet count (group 2). Thrombopoietin concentrations were lower in group 1 than in group 2 (92.5 (20.3–286.3) v 226.6 (30.1–848.3) pg/ml, p=0.003) and normal controls (92.5 (20.3–286.3) v 158.3 (22.5–232.9) pg/ml, p=0.028). Post-transplantation thrombopoietin concentrations increased with a peak at day 5. The rise was significant in patients with low pretransplantation platelet count (89.1 (21.29–247.6) to 545.1 (66.2–2569) pg/ml; n=16, p=0.001) but not in those with normal platelet count (262.8 (30.1–848.3) to 315.1 (114–954.6) pg/ml; n=7, p=0.47). No correlation was found pretransplantation between spleen volume and platelet count ( r =−0.11, p=0.6) or thrombopoietin concentrations ( r =−0.04, p=0.8). However, pretransplantation thrombopoietin concentrations correlated with platelet count ( r =0.47, p=0.0015), whereas an inverse correlation was found between peak thrombopoietin concentrations and nadir platelet count ( r =−0.41 p=0.049) post-transplantation. CONCLUSIONS: Inadequate thrombopoietin production may contribute to cirrhotic thrombocytopenia. Thrombopoietin production is restored after liver transplantation leading to the resolution of thrombocytopenia.